Does Trade Enhance Inclusive Growth? Empirical Evidence from Africa - Osei, A. (University of Ghana, 2020)
In March 2018, Africa created the largest free trade zone by membership. The African Continental Free Trade Agreement (AFCFTA) is expected to promote intra-regional trade, particularly among small scale enterprises hence greater inclusive economic growth. In this study, the researcher explored the relative impact of intra-regional trade and extra-regional trade on inclusive growth, measured by using the Asian Development Bank (AsDB) framework. Using data from 46 African countries covering 1995 to 2016, we estimated the impact of disaggregated trade flows (intra-regional trade and extra-regional trade) using the Spatial Tobit Panel Generalised Method of Moment (STPGMM) Estimator. The STPGMM allows us to control for potential spatial effect while eliminating potential biases and inconsistencies that may result from the tobit effect. The empirical evidence indicates that there is a significant positive relationship between both intra-regional and extra-regional trade and inclusive growth. In terms of magnitude, the evidence also indicates that the effect of extra-regional trade is higher compared with intra-regional trade on inclusive growth. Besides, the difference in the relative impacts of intra-regional and extra-regional trade, growth impact of intra-regional trade depended on political instability, market size, nature of commodities and excessive intervention and regional trade agreements. Accordingly, African countries must facilitate intra-regional trade to boost inclusive growth by reducing trade barriers, cost and promote infrastructure to enhance intra-regional trade in Africa.
MPhil. Finance
Keywords: Intra-regional trade; Extra-regional trade; Inclusive growth; Africa